2019
DOI: 10.1016/j.biopsycho.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal-level discrimination indices, sociodemographic factors, and telomere length in African-Americans and Whites

Abstract: Objective: Studies have linked self-reported discrimination to telomere attrition, a biological marker of accelerated cellular aging. However, it is unknown whether intersections between social categories—race, socioeconomic status (SES), sex, and age—influence the association of varying forms of discrimination with telomere length. We examined these associations in a socioeconomically and racially/ethnically diverse urban sample. Methods: Cross-sectional data were from 341 middle-aged (30–64 years) African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Another study of African American midlife men reported an interactive effect between racial discrimination and implicit in-group racial bias, with those reporting high levels of racial discrimination and holding an anti-Black bias having the shortest LTL, although there was no main effect of racial discrimination (Chae et al, 2014). These and other cross-sectional studies provide suggestive evidence that racial discrimination may have detrimental consequences for telomere shortening (Beatty Moody et al, 2019; Pantesco et al, 2018).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Another study of African American midlife men reported an interactive effect between racial discrimination and implicit in-group racial bias, with those reporting high levels of racial discrimination and holding an anti-Black bias having the shortest LTL, although there was no main effect of racial discrimination (Chae et al, 2014). These and other cross-sectional studies provide suggestive evidence that racial discrimination may have detrimental consequences for telomere shortening (Beatty Moody et al, 2019; Pantesco et al, 2018).…”
mentioning
confidence: 52%
“…Another study of African American midlife men reported an interactive effect between racial discrimination and implicit in-group racial bias, with those reporting high levels of racial discrimination and holding an anti-Black bias having the shortest LTL, although there was no main effect of racial discrimination . These and other cross-sectional studies provide suggestive evidence that racial discrimination may have detrimental consequences for telomere shortening (Beatty Moody et al, 2019;Pantesco et al, 2018). Some studies on race and telomere length have found no racial differences in telomere length or in fact longer telomeres among African Americans compared to Whites, likely due to pressures stemming from selection bias over time (Hamad, Tuljapurkar, & Rehkopf, 2016).…”
mentioning
confidence: 63%
“…A study of n = 1,026 found that higher parental SES was associated with 1.8% longer TL among newborn boys 20 . Another cross sectional study of n = 341 mixed race participants found that younger adults with higher burden of discrimination (race and sex) had shorter TL, while similar associations were reported among female from higher SES strata 21 . A recent longitudinal study of n = 1,031 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) reported that improvements in neighbourhood-level SES were protective on the rate of telomere attrition 22 .…”
Section: Introductionmentioning
confidence: 67%
“…A current gap regarding interpersonal-level discrimination research is that this multidimensional construct is traditionally assessed through emphasis on one aspect or domain of discriminatory experiences [15]. Specifically, while some research does assess several dimensions concurrently [e.g., [16][17][18][19][20][21], most research characterizing discrimination has not considered multiple facets of interpersonal discriminatory acts in a comprehensive manner, including their types (e.g., generic versus status specific [race-or gender-related]), context (e.g., workplace, court setting), frequency (e.g., daily, lifetime), form of threat (e.g., socio-emotional, physical), explicitness (e.g., covert versus overt), and consequences (e.g., posed obstacles, blocked opportunities). This is a particular limitation in descriptive discrimination research.…”
Section: Intersecting Sociodemographic Categories and Dimensions Of Discriminationmentioning
confidence: 99%